Pengembangan Rest Api Aplikasi EPerpus Sebagai Pengolah Sistem Informasi Perpustakaan - Yanuar Muhammad Bukhori; Selfi Artika (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The library information system is an application which is created to understand the flow of transaction processes in the library. Transactions in the library include the process of borrowing and returning books with manages overall data so that it helps in organizing the books in the library, the process of searching for books to be selected and displaying library transaction reports. The initial stage of the research was conducting surveys and interviews at the research location directly, where it was found that difficulties in the traditional library transaction process were obstacles in organizing books, borrowing and repaying transactions that spend a long time due to manual recording through diary reports. The results of the application are that it is hoped that all library staff work processes can be managed well, quickly, effectively, and efficiently.